2017
DOI: 10.3174/ajnr.a5299
|View full text |Cite
|
Sign up to set email alerts
|

3D Pseudocontinuous Arterial Spin-Labeling MR Imaging in the Preoperative Evaluation of Gliomas

Abstract: BACKGROUND AND PURPOSE:Previous studies showed conflicting results concerning the value of CBF maps obtained from arterial spin-labeling MR imaging in grading gliomas. This study was performed to investigate the effectiveness of CBF maps derived from 3D pseudocontinuous arterial spin-labeling in preoperatively assessing the grade, cellular proliferation, and prognosis of gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
(84 reference statements)
2
38
2
1
Order By: Relevance
“…Arterial spin labeling (ASL), as a noninvasive perfusion magnetic resonance (MR) imaging technique without administration of exogenous contrast agent, can qualitatively and quantitatively evaluate cerebral blood flow (CBF) whether under physiological or pathological conditions. Several researches have shown that ASL can help discriminate high- and low-grade gliomas [7], [8]. Although some studies [9], [10], [11], [12] suggested that CBF obtained from ASL may have relationships with histopathologic parameters, such as vascular density and epidermal growth factor receptor status.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial spin labeling (ASL), as a noninvasive perfusion magnetic resonance (MR) imaging technique without administration of exogenous contrast agent, can qualitatively and quantitatively evaluate cerebral blood flow (CBF) whether under physiological or pathological conditions. Several researches have shown that ASL can help discriminate high- and low-grade gliomas [7], [8]. Although some studies [9], [10], [11], [12] suggested that CBF obtained from ASL may have relationships with histopathologic parameters, such as vascular density and epidermal growth factor receptor status.…”
Section: Introductionmentioning
confidence: 99%
“…ASL, which provides absolute estimates of CBF, has been proved a valuable tool for adult patients with brain tumors for discriminating LGT and HGT. [10][11][12][13][14][15][16] However, adults and children have divergent tumor types, and the diagnostic value of ASL in pediatric brain tumors has not been fully investigated, to our knowledge.…”
mentioning
confidence: 99%
“…In a study by Zeng et al, 3D pCASL was performed in 58 patients with a confirmed diagnosis of gliomas in order to understand blood flow relative to WHO grading. 47 These authors found that relative CBF was significantly higher in high-grade gliomas than in low-grade gliomas. They also found that maximum CBF was a marker for both progression-free survival in gliomas and overall survival in glio-blastomas, with higher maximum relative CBFs leading to worse survival in patients with gliomas and better survival in those with glioblastomas.…”
Section: Gliomasmentioning
confidence: 96%
“…They also found that maximum CBF was a marker for both progression-free survival in gliomas and overall survival in glio-blastomas, with higher maximum relative CBFs leading to worse survival in patients with gliomas and better survival in those with glioblastomas. 47 Even subtle hyperperfused tumor tissue seen on ASL MRI has been associated with progression in Ki-67-positive glioblastoma (Fig. 3).…”
Section: Gliomasmentioning
confidence: 99%